Research design cassava pulp drying systems using drying equipment of three rounds dissociation drum - Tran, Văn Vang; Vo , Thành Một (Journal of Technical Education Science, 2014)
The drying equipment of three rounds dissociation drum is a new drying device which has been studied by several researchers. However, it is not still studied on drying cassava pulp in Viet Nam. It is made up of three cylinder pipes which are nested together, drying material and some agents that enter device from the last pipe, then go through the annular (gaps between cylinders) and exits out of the drum drying equipment. In the last pipe and annulars are arranged with the different wings to transport, stir drying metarial and enhance the moist heat exchange between the drying material and the drying agent. This device operates based on the principle of the combination of drum drying device and aerodynamic drying device. This article presents the results of research on cassava pulp drying design system using drum drying equipment of three rounds dissociation.